2021
DOI: 10.21203/rs.3.rs-955972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toxoplasma gondii is not an important contributor to poor reproductive performance of primiparous ewes from southern Australia: a prospective cohort study

Abstract: Background Toxoplasma gondii causes reproductive losses in sheep worldwide, including Australia. The reproductive performance of primiparous ewes is typically lower than for mature multiparous ewes, and younger ewes are more likely to be immunologically naïve and therefore more susceptible to reproductive disease if T. gondii infection occurs during pregnancy. The aim of this study was to assess the impact of infection with T. gondii on the reproductive performance of primiparous ewes in southern Australia u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…More recently, Chlamydia pecorum has been associated with abortions and stillbirth for maiden ewe flocks in Australia [ 35 , 36 ]. A recent study reported T. gondii, Neospora caninum and Coxiella burnetii were not important contributors to foetal and lamb mortality maiden ewe flocks on farms in southern Australia [ 37 , 38 , 39 ]. Immunological naïvety is considered a risk factor for infectious reproductive diseases, and therefore maiden ewes have a higher risk for infectious causes of abortion because they have had less time to be exposed to infection and develop immunity before pregnancy [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Chlamydia pecorum has been associated with abortions and stillbirth for maiden ewe flocks in Australia [ 35 , 36 ]. A recent study reported T. gondii, Neospora caninum and Coxiella burnetii were not important contributors to foetal and lamb mortality maiden ewe flocks on farms in southern Australia [ 37 , 38 , 39 ]. Immunological naïvety is considered a risk factor for infectious reproductive diseases, and therefore maiden ewes have a higher risk for infectious causes of abortion because they have had less time to be exposed to infection and develop immunity before pregnancy [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%